Charleston Ducote: capstone - Charleston, Ducote, artist (Colorado State University. Libraries, 2023)
The artist's statement: As both a biochemist and graphic designer, it is my calling to form bridges between seemingly disparate fields; science and art. Through visual communication, I aim to create new pathways of investigation and collaboration. I am a multimedia artist. I use everything from soft pastels to illustrator programs, to analogue video in order to communicate ideas and cultivate meaningful, interactive experiences. Good design can be the difference between exposure and obscurity for scientific publications. I use clean typesetting and concise imagery which convey complexity and beauty of my clients' work in an elegant, approachable way.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design